Situação atual e perspectivas de utilização de materiais no interior de aeronaves executivas - Costa, Fábio Rodrigues (Universidade Federal de São Carlos, 2009)
This study focuses on analyzing the current situation and perspectives of materials selection and utilization, like composites, decorative laminates and films, and others, in business aircraft, particularly in furnishings and its finishes, of great importance in this sector and systematically few studied. It was used technological prospective and competitive intelligence techniques like interviews with specialists, search in data and patents bases, analysis of existing studies and other sources. A case study was done on finishing materials, which are critical in the business aircraft class. Technological drivers for this sector, like air pollution reduction, personalization and simplicity of utilization, beyond others, were pointed out. It was verified that the materials selection is affected by several factors, namely: market segment involved, flight time and purpose and customer cultural differences, specially in relation to aesthetic, sensitive and comfort requirements; obligation to meet safety requirements from airworthiness agencies, specially in relation to inflammability and structural resistance and cabin safety; need of meeting design requirements, like low weight, high resistance/weight relation, fatigue resistance, degradation resistance, etc. In terms of patenting of cabin, interior and furnishings related technologies, Boeing, Airbus and Bombardier have been in highlighted position, while other business aircraft or interior manufacturers have appeared as owners of a relatively small number of patents. Important companies in key finishes (and their technologies) were identified by patents ownership. It was recommended that the materials selection and procurement process emphasizes the development and capability improvement of potential national suppliers, aiming at meeting business aviation requirements, as well as partnership with the relevant companies in patents ownership. A materials selection methodology was proposed, considering the researched context, which allows the maximization of aggregated value to the customer.
Current situation and perspectives of materials utilization in business aircraft interiors
Keywords: Engenharia de materiais; Prospecção tecnológica; Seleção de materiais; Aeronaves; Patentes; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA